Pengaruh Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK), Dan Pendapatan Asli Daerah (PAD) Terhadap Indeks Pembangunan Manusia (IPM) Di Kabupaten Tebo Provinsi Jambi Tahun 2020–2024 - Lisa Utari; Hariyadi .; Siti Hodijah; Nurhayani . (JOURNAL OF SHARIA ECONOMICS, 2025)
This study aims to analyze the effect of the General Allocation Fund (DAU), the Special Allocation Fund (DAK), and Local Own-Source Revenue (PAD) on the Human Development Index (HDI) in Tebo Regency, Jambi Province, during the 2020–2024 period. A quantitative method was applied using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) analysis.Data were collected from the Central Bureau of Statistics (BPS) and the Regional Financial and Asset Management Agency (BPKAD) of Tebo Regency. The results reveal that DAU, DAK, and PAD each have a positive and significant effect on HDI, with PAD being the most dominant variable. The coefficient of determination (R²) of 0.93 indicates that 93% of HDI variation can be explained by these three fiscal variables.This finding highlights the crucial role of effective fiscal governance and regional fiscal independence in promoting human development. Policy implications include performance-based budgeting, optimization of PAD potential, and prioritization of DAU and DAK allocation to education and health sectors